Kansei engineering and soft computing theory and practice - Dai, Ying 1963-; Chakraborty, Basabi 1956-; Shi, Minghui 1973- (Engineering Science Reference, 2011)
"This book focuses on the qualitative and quantitative evaluation of kansei, including the measurement and analysis of the impressions, emotions, and sense perceptions of groups and individuals, as well as the development of procedures for the representation, design and creation of products, machines and systems that embody the kansei of groups and individuals"--Provided by publisher.